DAMPAK APLIKASI FLY ASH DARI PEMBANGKIT LISTRIK DI PT. GREAT GIANT PINEAPPLE-LAMPUNG TERHADAP AKTIVITAS BIOLOGI TANAH DI LAHAN MARGINAL - Nurleni Kurniawati; Priyadi Priyadi (BPFP Universitas Bengkulu, 2021)
[EFFECT OF FLY ASH APPLICATION FROM POWER PLANT OF PT. GREAT GIANT PINEAPPLE ON SOIL BIOLOGYCAL ACTIVTY IN MARGINAL LAND]. Fly ash is a coal combustion waste containing nutrients that can be used to improve the soil fertility. The waste continues to increase but its handling is still limited because it is still classified as hazardous and toxic waste (B3). This study aims to determine the soil biological activity due to the application of fly ash and cow manure on marginal soils. The study was conducted using a completely randomized block design arranged factorial. The first factor is the dosage level of fly ash (F), namely 0 g/pot (0 ton/ha), 75 g/pot (50 ton/ha), 150 g/pot (100 ton/ha), and 225 g/pot (150 ton/ha) and the second factor is the dose of cow manure with three levels, namely 15 g/pot (10 ton/ha), 30 g/pot (20 ton/ha), and 45 g/pot (30 ton/ha). The observation parameters were (total population of fungi, bacteria, and soil respiration). The results showed that the addition of fly ash at various doses affected the soil biological activity by increasing the population of fungi, bacteria and soil respiration. The highest population of microorganisms was fungi, which was 17.8 x 107 Log CFU/g, bacteria 13.7 x 105 Log CFU/g, while the highest soil respiration was 54.53 mg CO2 at a dose of 100 ton/ha fly ash. In addition, the application of cow manure at a dose of 10, 20, 30 ton/ha did not affect observed variables.